2017
DOI: 10.3897/zookeys.652.10729
|View full text |Cite
|
Sign up to set email alerts
|

A literature-based review of Hymenoptera Parasitica and Chrysidoidea from Reunion Island

Abstract: A review of the genera and species of Hymenoptera Parasitica and Chrysidoidea reported so far from Reunion Island is provided with host information. Data presented here is based on a review of the existing literature by the authors. The list includes: (1) 156 species of Ichneumonoidea belonging to 65 genera and 25 subfamilies (Braconidae:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 92 publications
0
1
0
Order By: Relevance
“…In larger instars, the presence of Apanteles sp. as parasitoids which attacks larvae also plays a role in reducing the number of larvae (Gupta et al, 2016;Hasanah et al, 2018;Mardiningsih et al, 2010;Muru et al, 2017). At the time of this study, the smallest larvae found to be attacked by this parasitoid were the fourth instar.…”
Section: Resultsmentioning
confidence: 66%
“…In larger instars, the presence of Apanteles sp. as parasitoids which attacks larvae also plays a role in reducing the number of larvae (Gupta et al, 2016;Hasanah et al, 2018;Mardiningsih et al, 2010;Muru et al, 2017). At the time of this study, the smallest larvae found to be attacked by this parasitoid were the fourth instar.…”
Section: Resultsmentioning
confidence: 66%